Structural diversity of CuZn₂InSe₄ quaternary chalcogenides: electronic and phonon properties from first principles - Ma, Long (2023)
First principles simulations are utilized to calculate the electronic and vibrational properties of several metastable structural phases of the CuZn2InSe4 quaternary chalcogenide, including stanite, kesterite, primitive mixed CuAu, wurtzite-stanite, and wurtzite-kesterite lattices. We find that although each phase is formed by nearest cation-chalcogen bonds, the structural diversity due to cation and polyhedral arrangements has direct consequences in the electronic structure. The simulations further indicate that hybrid functionals are needed to account for the s-p and p-d orbital hybridization that is found around the Fermi level, which leads to much enhanced energy band gaps when compared with standard exchange-correlation approaches. We also find that the thermal conductivities for all phases are relatively low, and the main scattering channel comes from a low frequency optical band hybridized with acoustic phonons. Given that CuZn2InSe4 is a material from a larger class of quaternary chalcogenides, other materials may exhibit similar electronic and vibrational properties, which may be useful for electronic and thermal management applications.